(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Single phase AC-DC bridgeless SEPIC power factor correction (PFC) rectifier in discontinuous conduction mode is proposed. In this topology conduction losses are less with improved thermal management. During each switching cycle two semiconductor switches are only present in current flowing path. In a effective simple manner unity power factor is achieved through discontinuous conduction mode. Control circuit complexity is reduced by soft switching of power switches and zero current turn off of output diode. Conventional SEPIC PFC rectifier is compared with the proposed topology. PI controller compensates the error and maintains unity power factor. The results obtained from simulation and experiment show the effectiveness of the proposed topology.